Induction and Amelioration of Methotrexate-Induced Gastrointestinal Toxicity are Related to Immune Response and Gut MicrobiotaResearch in context - Bailing Zhou; Xuyang Xia; Peiqi Wang; Shuang Chen; Chaoheng Yu; Rong Huang; Rui Zhang; Yantai Wang; Lian Lu; Fengjiao Yuan; Yaomei Tian; Yingzi Fan; et al. (EBioMedicine, 2018)
As a widely used anticancer and immunosuppressive agent, methotrexate (MTX) can induce multiple adverse drug reactions (ADRs), such as gastrointestinal toxicity, the mechanisms are poorly understood. Gut microbiota has been widely reported to be associated with the onset of multiple diseases as well as treatment outcomes of different drugs. In this study, mucosal injury was observed in MTX-treated mice, leading to significant changes in macrophages (i.e., M1/M2 ratio, P < 0.05) but not in dendritic cells. Moreover, the population, diversity and principal components of the gut microbiota in mice were dramatically altered after MTX treatment in a time-dependent manner, and Bacteroidales exhibited the most distinct variation among all the taxa (P < 0.05). Bacteroides fragilis was significantly decreased with MTX treatment (P < 0.01) and tended to decrease proportionately with increasing macrophage density. Gavage of mice with B. fragilis ameliorated MTX-induced inflammatory reactions and modulate macrophage polarization. In conclusion, our results delineate a strong impact of the gut microbiota on MTX-induced intestinal mucositis and provide a potential method for the prevention of such ADRs. Keywords: Methotrexate, Gastrointestinal toxicity, Gut microbiota, Mononuclear phagocyte